2010
DOI: 10.2981/07-040
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of the relationship between red fox Vulpes vulpes and its prey species (grey partridge Perdix perdix, brown hare Lepus europaeus and rabbit Oryctolagus cuniculus) in Western Germany from 1958 to 1998

Abstract: Predator-prey relationships are of general interest in ecology and have been studied extensively. They are also of interest for effective management and recovery of prey populations. However, quantification of these relationships in the field has remained difficult. We analysed the impact of the predation of red fox Vulpes vulpes on brown hare Lepus europaeus, grey partridge Perdix perdix and rabbit Oryctolagus cuniculus using yearly hunting bag records as population indicators in eight German provinces over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…Experimental evidence showed that culling badgers for disease control was associated with increases in fox densities (Trewby et al 2008). In turn, the fox is generally acknowledged as the main predator of the brown hare throughout Europe and under some circumstances it is considered that fox predation may influence hare densities (Knauer et al 2010;Reynolds et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence showed that culling badgers for disease control was associated with increases in fox densities (Trewby et al 2008). In turn, the fox is generally acknowledged as the main predator of the brown hare throughout Europe and under some circumstances it is considered that fox predation may influence hare densities (Knauer et al 2010;Reynolds et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We focused on red fox (Vulpes vulpes) as the main predator of European hare and European rabbit (Oryctolagus cuniculus) as the main competitor of European hare. Red fox can substantially impact hare populations as a predator (Knauer, Küchenhoff, & Pilz, 2010;Schmidt, Asferg, & Forchhammer, 2004). European hares and rabbits have a substantial overlap in resources (Kuijper, van Wieren, & Bakker, 2004) and are classified as trophic competitors when sympatric (Homolka, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Hunting data are a commonly used source of ungulate indices at large spatial scales and for long periods where other sources are not available (e.g. [4446]). Given the similar social conditions and the use of same hunting system across the study area, we ruled out different intensity of hunting efforts as a possible reason for significant differences in ungulate density and total biomass in Beskydy and Orava.…”
Section: Methodsmentioning
confidence: 99%